2016
DOI: 10.1111/hae.12939
|View full text |Cite
|
Sign up to set email alerts
|

Low thrombin generation during major orthopaedic surgery fails to predict the bleeding risk in inhibitor patients treated with bypassing agents

Abstract: This study fails to support a definite role for the TG assay as a reliable laboratory tool to monitor the haemostatic efficacy of bypassing therapies and as a predictor of the risk of bleeding in inhibitor patients using these agents during orthopaedic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The use of the thrombin generation assay (TGA) has been proposed to individually tailor bypassing therapy and/or to monitor the efficacy of such therapy in patients undergoing surgery but with non-univocal results. 6,7 Recently, Dargaud et al proposed the use of TGA as a helpful tool to limit adverse events that may occur when emicizumab is used in association with other hemostatic drugs as in the occasion of treatment of breakthrough bleeds. 4 In fact, in the HAVEN 1 study (NCT02622321), thrombotic microangiopathy and thrombosis were reported in 5 patients who received multiple doses of aPCC >100 IU/kg for more than 24 hours to treat breakthrough bleeds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the thrombin generation assay (TGA) has been proposed to individually tailor bypassing therapy and/or to monitor the efficacy of such therapy in patients undergoing surgery but with non-univocal results. 6,7 Recently, Dargaud et al proposed the use of TGA as a helpful tool to limit adverse events that may occur when emicizumab is used in association with other hemostatic drugs as in the occasion of treatment of breakthrough bleeds. 4 In fact, in the HAVEN 1 study (NCT02622321), thrombotic microangiopathy and thrombosis were reported in 5 patients who received multiple doses of aPCC >100 IU/kg for more than 24 hours to treat breakthrough bleeds.…”
mentioning
confidence: 99%
“…On the occasion of the second procedure, TGA (see below) was used to measure coagulation activation ex vivo after the administration of bypassing agents, both pre-operatively in a non-bleeding state (testing two different doses of rFVIIa and aPCC) and then during the peri-operative period, as previously reported. 7 In 2017, while on regular prophylaxis with emicizumab 1.5 mg/kg/week in the frame of the HAVEN 1 trial (NCT02622321), 2 the patient required a right hip replacement due to the displacement of the screws used to fix the femoral fracture. Based on our local practice and protocol recommendations, 2 we chose rFVIIa to manage the surgery.…”
mentioning
confidence: 99%
“…Mancuso et al present their observations around major orthopaedic surgery with the aim of advancing the monitoring of clinical efficacy of bypassing agents. Following on from some evidence in in vitro with inconsistent ex vivo studies, Mancuso et al conclude that thrombin generation assay (TGA) fails as a reliable laboratory tool to monitor haemostatic efficacy and as a predictor of the risk of bleeding in inhibitor patients undergoing orthopaedic surgery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inter-or even intra-individual clinical phenotypic heterogeneity may emerge in patients with the same residual coagulation factor activity, as well as different haemostatic and clinical outcomes during the same medication and dosage may occur (5)(6)(7)(8). Therefore, there is a strong demand for an exploratory modality concerning the dynamics of global haemostasis, and the biological and clinical impact of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A reliable, simple and easily accessible, preferably bed-side test has been a long-awaited tool for monitoring the haemostatic performance of haemophilia therapies in life-threatening bleedings or for preventing such bleeds. In haemophilia with inhibitors and surgery it gains the significance of life-saving importance (7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%